Effects of Rainfall on Mechanical Behaviors of Residual-Soil Landslide - He, Yong; Yu, Zhi-Peng; Zhang, Zhao; Chen, Bin; Zhang, Ke-Neng (Frontiers in Earth Science, 2022)
Rainfall-induced landslides commonly occur in residual-soil layers of Chenzhou city, China. Slope failure induced by rainfall is intimately related to changes in the mechanical property and microstructures of residual soils. In this study, series of direct shear tests were respectively conducted on four typical residual soils from the area of Chenzhou to study influences of rainwater on their mechanical behaviors. Meanwhile, X-ray diffraction (XRD) tests and scanning electron microscope (SEM) tests were also performed to investigate microstructure characteristic of several types of soils. Experimental results revealed that the shear strength of soils decreased with increasing water content and its development trends were obviously influenced by the types of residual soils. Meanwhile, the shear strength of soils increased with the increase of vertical loads, and the relationship between them could be well expressed by a linear function. As water content increased, the calculated cohesions and internal friction angles both decreased. XRD observations implied that several residual soils showed rich clay minerals, including pyrophyllite, illite, kaolinite and montmorillonite, etc. Microstructures of these soils presented a sheet-structure system which was composed of various-sized clay particles. During hydration, these clay minerals gradually transferred from a face-face arrangement to face-edge or even edge-edge one, leading to the softening of clay particles and the reduction of the contact force between soil particles.